Who's afraid of Homo sapiens? - Preuss, Todd M (BioMed Central, 2006)
Understanding how humans differ from other animals, as well as how we are like them, requires comparative investigations. For the purpose of documenting the distinctive features of humans, the most informative research involves comparing humans to our closest relatives–the chimpanzees and other great apes. Psychology and anthropology have maintained a tradition of empirical comparative research on human specializations of cognition. The neurosciences, by contrast, have been dominated by the model-animal research paradigm, which presupposes the commonality of "basic" features of brain organization across species and discourages serious treatment of species differences. As a result, the neurosciences have made little progress in understanding human brain specializations. Recent developments in neuroimaging, genomics, and other non-invasive techniques make it possible to directly compare humans and nonhuman species at levels of organization that were previously inaccessible, offering the hope of gaining a better understanding of the species-specific features of the human brain. This hope will be dashed, however, if chimpanzees and other great ape species become unavailable for even non-invasive research.